The effect of profitability, growth opportunity, leverage, and firm size on cash holding - Kiki Kusmarahati Maryanto; Yuli Tri Cahyono (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine and analyze the effect of Profitability, Growth Opportunity, Leverage and Firm Size on Cash Holding in manufacturing companies in the food and beverage sub-sector industry listed on the Indonesia Stock Exchange for the 2019-2022 period. The research method used in this research is quantitative method. The data used is secondary data, namely in the form of annual reports and financial data on manufacturing companies in the food and beverage sub-sector industry sector from 2019 to 2022. The sampling method used purposive sampling method and obtained 18 sample companies for four years of observation (2019-2022) so that there were 72 samples. Hypothesis testing in this study using multiple linear regression analysis. The results showed that partially Profitability has an effect, while Growth Opportunity, Leverage and Firm Size have no effect on Cash Holding.